Two new species of fungi - and R.C. RAJAK, U.S. PATEL, A.K. PANDEY (Indian Phytopathology, 2002)
Two new species of saprophytic fungi, Ohleria phyllanthicolla and Parapericonia indica, collected from the South Shahdol forest division, Madhya Pradesh, India, from Bambusa arundinacea and Butea monosperma respectively, are described, illustrated and compared with allied species.